2020
DOI: 10.1038/s41598-020-67394-8
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive uric acid electrochemical biosensor based on a nano-cube cuprous oxide/ferrocene/uricase modified glassy carbon electrode

Abstract: A uric acid (UA) electrochemical biosensor was constructed using ferrocene (fc) decorated cuprous oxide (cu 2 o) enhanced electro-active characteristics and covalently immobilized with uricase (Uox) on glassy carbon electrode (Gce). the electrochemical characteristics of the fabricated electrode was analysed by cyclic voltammetry, electrochemical impedance spectroscopy and differential pulse voltammetry (DpV). DpV studies revealed rapid response of fabricated electrode Uox/fc/cu 2 o/Gce towards UA in a wide co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 37 publications
(35 reference statements)
3
44
0
Order By: Relevance
“…The obtained value of sensitivity is much higher than the ones reported in literature (3 to 40 (µA)mM −1 ) for other uric acid biosensors [23,24]. Ya et al [25] has recently reported a uric acid biosensor based on Cu 2 O nanoparticles on glassy carbon electrode and further decorated with ferrocene and reported a sensitivity of 1.9 µA/(mM-cm 2 ). Kudo et al [26] reported a uric acid biosensor based on the measurement of H 2 O 2 produced in the enzymatic reaction and obtained a sensitivity of 170 nA/mM in saliva.…”
Section: Sensing Of Uric Acidmentioning
confidence: 59%
“…The obtained value of sensitivity is much higher than the ones reported in literature (3 to 40 (µA)mM −1 ) for other uric acid biosensors [23,24]. Ya et al [25] has recently reported a uric acid biosensor based on Cu 2 O nanoparticles on glassy carbon electrode and further decorated with ferrocene and reported a sensitivity of 1.9 µA/(mM-cm 2 ). Kudo et al [26] reported a uric acid biosensor based on the measurement of H 2 O 2 produced in the enzymatic reaction and obtained a sensitivity of 170 nA/mM in saliva.…”
Section: Sensing Of Uric Acidmentioning
confidence: 59%
“…So, we can assume that our suggested procedure can be applied for the indirect quantification of MEB. Well-dispersed Cu 2 ONPs-C over graphite grain surfaces was beneficial for the electrocatalytic reaction that may occur at the electrode surface [18]. The markable enhancement of Cu + oxidation current indicates the electrocatalytic activity of the Cu 2 ONPs-C@G, which can be attributed to synergistic electrochemical activity between Cu 2 ONPs-C and graphite grain surfaces, which in turn can be illustrated as the existence of the Cu + /Cu 2+ redox couple, making the electrode surface highly sensitive.…”
Section: Electrochemical Behavior Of Meb On the Cu 2 Onps-c@g/pementioning
confidence: 99%
“…Because of these properties, metal and metal oxide nanoparticles have been used successfully for increasing carbon paste electrode sensitivity toward various electroanalytical applications [15,16]. It was found in the literature that pure Cu2ONPs [11] and Cu2ONPs supported on carbon materials were applied successfully in different voltametric determinations [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Intercalation of propoxur with layered zinc hydroxide produces a nanocomposite material that has good electron transfer ability and a large surface-tovolume ratio. It has also been reported that this material shows low toxicity, high thermal stability, biocompatibility and the potential for controlled release [26,27]. Based on the listed advantages, in this work, we are presenting for the first time LZH-SDS-PRO material as a mediator used to increase the electrocatalytic activity of the redox reaction important for the determination of UA.…”
Section: Introductionmentioning
confidence: 99%